Pendampingan Pengelolaan Google Maps Bagi Pelaku UMKM di Kelurahan Padang Sukamara Kalimantan Tengah - Helmina, Helmina; Ahmad, Sabarudin; Ahmidi, Ahmidi (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to provide assistance to Micro, Small, and Medium Enterprises (MSMEs) in Padang Village, Sukamara Regency, Central Kalimantan, in utilizing Google Maps as a digital promotional medium. The implementation method included education and technical training on creating business accounts on Google Maps. The results of the activity showed that participants were able to create and manage business profiles on Google Maps, adding locations, operating hours, contacts, and product photos, thereby increasing their business visibility in the digital realm. This mentoring activity contributed to strengthening the capacity of digital MSMEs and encouraging the development of a technology-based local economy.